2006
DOI: 10.1002/sia.2507
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy imaging of ZnO nanodots deposited on quartz by sparking off different tip shapes

Abstract: We have demonstrated a simple method for depositing ZnO nanodots on quartz substrates by sparking off different tip shapes at voltages of 2, 4 and 6 kV in air at atmospheric pressure. A comparison was made among the three tip shapes: the sharp tip, the conical tip and the dull tip. The surface morphology was then observed by atomic force microscopy. The mean height of the randomly distributed dots of approximately 8 nm was successfully deposited from the sharp tip at 6 kV. Characterizations by UV-vis spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A probable reason is that the grain size measured from AFM is the surface morphology of coalesced grains which gives the particle size, the other reason for that is the effects of AFM tip‐shape. T. Kumpika et al suggested that the mean size of grain is prepared from the conical tip, which was larger than the sharp tip . Nevertheless, it can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A probable reason is that the grain size measured from AFM is the surface morphology of coalesced grains which gives the particle size, the other reason for that is the effects of AFM tip‐shape. T. Kumpika et al suggested that the mean size of grain is prepared from the conical tip, which was larger than the sharp tip . Nevertheless, it can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bombardment of electrons and ions produced aluminum nanoparticles that were oxidized in air and deposited onto underlying substrates. 18 After that, the samples were annealed in air at various temperatures for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…The related literature includes only a few applications on the preparation of nanoparticles (NPs), derived from the material(s) of the electrodes between which the sparking occurs [3,4], the deposition of them onto solid substrates [5][6][7], and the development of nanostructures [8,9].…”
Section: Introductionmentioning
confidence: 99%